Kesenjangan Layanan Konseling Pendekatan Rational Emotive Behavior Therapy terhadap Kode Etik Profesi Bimbingan dan Konseling - Kusumaningrum, Nimas Safitri; Zain, Nurul Azizah; Nurarifin, Nita Ariska; Pangesti, Tita (JURNAL KONSELING GUSJIGANG, 2018)
Counselor Give the facility on Counseling must use a theory approaches who are appropriate with the problem of student. But in the reality, Counselour argue that not all of proccess of Counseling must using approaches and theory of Counseling. Counselor just see from problem it self. The goal of this research is to know about the understanding of Counselour using REBT Theraphy. This Research using Survey Methode who are using multiple choice who are contain the understanding of REBT. Sample who are used is using technique Random Sampling involved 7 Counselor in Cepu District.Based on the research get score 76,4 who are in middle of the category. Based on from points the highest on 23% is about the understanding about the theory and the smallest is about Principal about REBT approaches on 17%. The Result can be the consider to Counselour to get implemantation about facility Guidance and Counseling to increase the skill or pedagogical skill appropriately with Ethic of Counselor